One-pot in-situ hydrothermal synthesis of VSe2/MoSe2 nanocomposite for enhanced hydrogen evolution reaction - M. Alahmadi; Sami Ben Aoun (Arabian Journal of Chemistry, 2023)
Hydrogen is the kind of pure, renewable energy that is required for the world to begin relying less and less on the fossil fuels that it currently consumes. The production of hydrogen by electrocatalytic water splitting is deemed to be preferable to the consumption of fossil fuels for the generation of clean and reliable energy. A catalyst's ability to catalyze is significantly influenced by the number of exposed active sites in the catalyst. Thus, the purpose of the current work is to offer a simple and inexpensive strategy to synthesize a double non-noble metal catalyst of VSe2/MoSe2 via one-step hydrothermal synthesis for catalytic Hydrogen evolution reaction (HER). The strong and unique orientation interaction between the nanosheet-like structure of VSe2 and the nanoflower-like structure of MoSe2 in the nanocomposite significantly improved the electron transfer kinetics. Subsequently, the electrochemical hydrogen production performance of the hybrid VSe2/MoSe2 is enhanced as compared to its constituent materials. Electrochemical characterizations prove that the VSe2/MoSe2 nanocomposite enhances the electrochemical activity performance with the lowest onset potential (330 mV) and a low value of Tafel plot (66 mV/decade) in comparison with sole MoSe2 and VSe2. In addition, the nanocomposite shows a low charge transfer resistance of 65 Ω, which further advocates the HER polarization curve and Tafel plot.